Design and Build a Home Security System based on an ESP32 Cam Microcontroller with Telegram Notification - Filantropi Yusuf Aji Cahyono; Nugroho Suharto; Lis Diana Mustafa (Jurnal Jaringan Telekomunikasi, 2022)
Along with the times and technology, the need for fast information is needed in various sectors of life, thus supporting the performance of these sectors, one of which is the security aspect, especially in security at home, considering that there are many things that happen such as crimes and negligence of residents of the house that can cause problems such as fires. In this case, a system is needed that can visually monitor the condition of the room from remote location. This is useful for the surveillance process so that if there is a crime and fire in the surveillance room, the system can monitor the state of a room via a smartphone. This study aims to create a device that is able to increase the security of the room at home by utilizing the Esp32 cam as a microcontroller and the PIR sensor as a detector of movement when crossing the corner area of the sensor and also the Fire sensor key as a detector of fire. In this study, the ESP32 cam is used as the main brain of the system which will read data from the fire sensor, PIR sensor, and remotely control the door lock and door unlock. The data from the sensor will be sent to the server by Esp32 cam. The test results have been running in accordance with the designed system. So that pictures taken and notifications of fire can be sent to the telegram application with a 100% success percentage.